Sleepless in Singapore - Sim, Jack (Institutional Knowledge at Singapore Management University, 2008)
Is it time for Singapore to adopt a new social and business model? Jack Sim, the inimitable founder of World Toilet Organization, unveils his ‘not-so-wild-and-far-fetched’ vision of a timeless zone in Singapore.